Aligned High Density Semi‐Conductive Ultra‐Small Single‐Walled Carbon Nanotubes. Issue 43 (26th November 2019) - Wang, Yun; Ben, Teng; Qiu, Shilun; Valtchev, Valentin
Abstract: Zeolite type material (AlPO‐5, AFI‐type) with rod‐like morphology and mono‐dimensional channel system running along the long crystal axis was vertically grown on a stainless‐steel plate. The organic template used in the synthesis was carbonized to generate single‐walled carbon nanotubes (SWCNTs). Thus, SWCNTs with a diameter of 0.4 nm, perfectly aligned and vertically oriented to the support surface with a density of 2.6 × 10 5 SWCNTs μm −2, were obtained. The free end of AlPO‐5 crystal was chemically etched in order to create contact surface and measure the conductivity of SWCNT@AlPO‐5 film which was found to be 4.16 × 10 −1 Ω −1 cm −1 . This approach of aligned SWCNTs can be applied to different types of substrates, thus opening the road to practical uses of SWCNTs. Abstract : Aligned ultra‐small single‐wall carbon nanotubes: Carbonization of organic template in AlPO‐5 molecular sieves is used to generate SWCNTs, and after controlled etching to create contact surface that allows to explore their semi‐conductive properties.